(untitled) (Desenvolvimento em Questão, 2024)
The gradual increase in population requires food production to follow its evolution, however, in a sustainable way and in balance with the environment. The research aims to identify the environmental practices of livestock in properties in the Municipality of Nova Marilândia – Mato Grosso/Brazil. The research is characterized by the descriptive type, qualitative approach, and used the case study strategy. The collection instruments were semi-structured forms, interviews and on-site observation. Four producers who have livestock as their activity participated in the research. Initially, which environmental practices are used in livestock management were identified. The results revealed that most properties do not use sustainable environmental practices, however, they perform some actions partially and that comply with environmental legislation